POPPY II Cohort Profile– a population-based linked cohort examining the patterns and outcomes of prescription opioid use in NSW, Australia, 2003-2018. - Gisev, Natasa; Pearson, Sallie-Anne; Dobbins, Timothy; Buizen, Luke; Murphy, Tom; Wilson, Andrew; Blyth, Fiona; Dunlop, Adrian; Larney, Sarah; Currow, David C.; Mattick, Richard P.; Degenhardt, Louisa (International Journal of Population Data Science, 2022)
Objectives Although opioid prescribing and harms have increased in Australia, there is a lack of population-level evidence about the drivers of long-term opioid use, dependence and other harms. This study aims to profile the POPPY II cohort, with respect to sociodemographic and clinical health characteristics and patterns of opioid initiation. Approach The POPPY II cohort includes adult residents (≥18 years) in NSW who were initiated on prescribed opioids subsidised through Australia’s Pharmaceutical Benefits Scheme for any period between 1st July 2003 and 31st December 2018. The cohort has been linked to nine other datasets containing information on socio-demographic and clinical characteristics, health service use, and adverse outcomes. Results There were 3,569,433 people in the cohort. One in four people were aged ≥65 years at the time of opioid initiation (26.8%) and half were female (52.7%). About 71% resided in a major city. Approximately 6% had evidence of being treated for cancer in the year prior to opioid initiation (5.8%). In the 3 months prior to cohort entry, 27% used an analgesic medicine and 21% used a psychotropic medicine. Less than a third initiated on a strong opioid (22.2%) and the most commonly initiated opioid was paracetamol/codeine (61.3%). Conclusion The POPPY II study is the largest post-marketing surveillance study of prescribed opioids in Australia, and one of the largest studies worldwide. Understanding the characteristics of the cohort will inform future work aimed at generating robust evidence of the long-terms patterns and outcomes of prescribed opioid use in the Australian community.